The risk of defects in the neural tube caused by valproic acid and carbamazepine (2005)
Objective. To determine the risk, if any, of carbamazepine and valproic acid use on the foetus with respect to neural tube defects. Materials and methods. Databases such as MEDLINE, EMBASE, SCISEARCH, The Cochrane Library and LILACS were consulted to have access to published literature from January 1966 to September 2004. All articles published in English and Spanish were considered. A manual review of the references presented in each produced article was done in order to identify the articles that the electronic search may have not found itself. However, articles which seemed ambiguous as to the title and/or abstract were completely analyzed to establish their relevance. Studies that examined the effects of systematic exposure to carbamazepine or valproic acid during pregnancy and that assessed neural tube defects in the infants were eligible. The data was extracted in the form of 2 x 2 tables. The odds ratio (OR), relative risk (RR) and 95% confidence interval (CI) was calculated for each of the studies. Results. The pooled relative risk of neural tube defects among the exposed to valproic acid was 0.61 (95% CI: 0.06-6.72). The risk among the exposed to carbamazepine was 1.10 (95% CI: 0.16-7-75). Conclusions. Due to the methodologic limitations of most of the studies where the data was insufficient, only three studies could be included in the meta-analysis. There is not enough evidence to establish the risk raised in the objective of the study. © 2005, Revista de Neurología.